Resistance to carbapenems by Acinetobacter spp. reported to GLASS according to the income level of the countries (Research, Society and Development, 2021)
This work aims to evaluate the resistance to carbapenems of Acinetobacter spp. reported to the GLASS (Global Antimicrobial Resistance and Use Surveillance System), stratifying these data by per capita income bracket. A retrospective observational study was conducted on carbapenem sensitivity of Acinetobacter spp., reported to GLASS, including all data available at the time of collection, february 2021, stratifying these findings by each country's income level and number of tests of sensitivity to carbapenemics performed. Higher-income countries had the lowest reported non-susceptibility, yet within them there are examples that have a high incidence of non-susceptibility. For all four income groups there was a high standard deviation variance for the mean of the carbapenem sensitivity tests, thus revealing points of inconsistency. The data worked in this article show a worrying level of resistance to carbapenems observed in GLASS. Even within rich countries, there are those that have alarming levels of non-susceptibility, and for the poorest countries, there is a lack of more complete data, because in those with the most worrying levels of non-susceptibility, strains of Acinetobacter spp. are already found with multidrug resistance phenotype.